The Role of BMT in Increasing Islamic Financial Literacy in Society (Case Study in BMT Amanah Ummat Taram Kecamatan Harau) - Hebby Rahmatul Utamy; Muhammad Deni Putra; Frida Amelia; Wahyu Putra Utama (Department of Islamic Economics, Islamic University of Indonesia, 2020)
One of the reasons for the low public transactions in Islamic banks is their low Islamic financial literacy. Financial literacy is the level of knowledge, skills, trust in financial institutions, along with their products and services. The objective of this research is to understand the role of BMT in increasing Islamic financial literacy among society. This study is field research in nature. The study employed descriptive analysis with a qualitative approach, and the data were collected through interviews and documentation. The study was conducted in BMT Amanah Ummat Taram, Kecamatan Harau, Kabupaten Limapuluh Kota. The result showed that Islamic financial literacy is of the utmost importance in society. The society could carry out economic activities under Islamic law and start to move from conventional financial institutions to Islamic financial institutions, such as BMT. Efforts have been taken by BMT to increase Islamic financial literacy. These efforts are the socialization of the Islamic economy, communal Qur’an reading, and skill coaching to improve the quality of internal human resources. Improvements in BMT efforts are including introducing transaction agreements and BMT products to increase customers’ knowledge, promoting products and services through social media to increase customers’ trust, and educating financial management and saving to increase customers’ skills. The main obstacles faced by BMT in their efforts increase Islamic financial literacy is the mindset of the society, education, and lack of skilled and competent staff.